Superintegrable and scale invariant quantum systems with position dependent mass - Nikitin, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9 Scale invariant Schrödinger equations with position dependent mass admitting second order integrals of motion are classified.